Autodesk AutoCAD : 2014 (2D) essentials - Baker, Stephen (Digital classroom (Indianapolis, Ind.), 2014)
"Master AutoCAD 2014 on your own terms with this one-of-a-kind video training course. AutoCAD is the industry-leading architectural and drafting software, and AutoCAD 2014 is packed with the tools you need to create impressive CAD projects and designs. Now, you can learn the ins and outs of maximizing AutoCAD 2014 - from setting up your drawing environment to using text, dimensions, hatching, and more - with Autodesk AutoCAD 2014 Essentials. Our instructors provide expert, straight-forward, user-friendly training to help you tackle new topics the way you want to learn. Master basic skills, boost your creativity, and challenge yourself in bold new directions. Familiarize yourself with AutoCAD basics like using the interface and command window, navigating through menus, and creating your first drawing Understand drafting methods and tools, draw with blocks, and manage layers Improve your workflow with templates, project standards, and objects Discover how to use hatches and work with drawings, dimensions, and 3D modeling Includes over 6 hours of AutoCAD 2014 video training. If you're looking for real-world AutoCAD 2014 instruction, you'll find it here."--Resource description page.